2008
DOI: 10.1029/2008je003185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesoscale gravity waves in the upper and lower clouds of Venus from VEX‐VIRTIS images

Abstract: Images obtained from the Visible and InfraRed Thermal Imaging Spectrometer (VIRTIS)‐M instrument onboard Venus Express present visible trains of alternating bands of cloud brightness in two different layers: at the upper cloud tops (∼66 km altitude) observed in the dayside hemisphere using reflected ultraviolet light (380 nm) and in the lower cloud (∼47 km altitude) observed in the nightside hemisphere using thermal radiation (1.74 μm). The waves are nearly zonal (with the bands perpendicular to latitude circl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 56 publications
7
69
0
Order By: Relevance
“…Recent numerical studies suggest that both the thermal tide (e.g., Matsuda 2006, 2007) and meridional circulation mechanisms (e.g., Yamamoto and Takahashi 2004) might be viable in the Venusian atmosphere, in which the vertical and horizontal transport of angular momentum due to thermal tides, eddies, and mean meridional circulation plays an important role. Other kinds of waves, such as the four-and fiveday waves found in UV images of the cloud top (e.g., Del Kouyama et al 2013Kouyama et al , 2015 and small-scale disturbances suspected to be related to gravity waves (e.g., Sagdeev et al 1986;Hinson and Jenkins 1995;Peralta et al 2008;Garcia et al 2009) may also play important roles in the establishment and maintenance of the atmosphere's super-rotation. Schubert et al (1980) suggested that the zonal-mean meridional circulation consists of several vertically stacked cells extending from the equator to poles, based on wind profiles obtained by entry probes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent numerical studies suggest that both the thermal tide (e.g., Matsuda 2006, 2007) and meridional circulation mechanisms (e.g., Yamamoto and Takahashi 2004) might be viable in the Venusian atmosphere, in which the vertical and horizontal transport of angular momentum due to thermal tides, eddies, and mean meridional circulation plays an important role. Other kinds of waves, such as the four-and fiveday waves found in UV images of the cloud top (e.g., Del Kouyama et al 2013Kouyama et al , 2015 and small-scale disturbances suspected to be related to gravity waves (e.g., Sagdeev et al 1986;Hinson and Jenkins 1995;Peralta et al 2008;Garcia et al 2009) may also play important roles in the establishment and maintenance of the atmosphere's super-rotation. Schubert et al (1980) suggested that the zonal-mean meridional circulation consists of several vertically stacked cells extending from the equator to poles, based on wind profiles obtained by entry probes.…”
Section: Introductionmentioning
confidence: 99%
“…We have no observational results as yet for the zonally averaged meridional circulation in the Venusian atmosphere. To elucidate the dynamical effects of meridional circulation, waves, and eddies, their threedimensional structures on both the dayside and nightside must be understood (Peralta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The specific disturbance that provides energy to the Kelvin wave has not been identified. Small-scale atmospheric structures indicative of internal gravity waves were observed in temperature profiles (Hinson and Jenkins, 1995) and in cloud images Peralta et al, 2008). Oscillating vertical winds encountered by Vega balloons over highlands are attribute to orographically-excited gravity waves (Sagdeev et al, 1986); orographic waves, however, should transport eastward momentum upward and decelerate the super-rotation.…”
Section: Super-rotationmentioning
confidence: 99%
“…VEX/VIRTIS-M images revealed numerous mesoscale waves in the upper and lower atmosphere (Peralta et al 2008), confined to poleward of 40°S. Because of VEX's polar orbit, however, detection of waves might have been biased to higher southern latitudes.…”
Section: Atmospheric Dynamicsmentioning
confidence: 99%